The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fpsyg.2016.01772
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Social Evaluation, Social Eavesdropping, Reputation Formation, Image Scoring or What You Will

Abstract: Social evaluation is a mental process that leverages the preference toward prosocial partners (positivity bias) against the avoidance of antisocial individuals (negativity bias) in a cooperative context. The phenomenon is well-known in humans, and recently comparative investigations looked at the possible evolutionary origins. So far social evaluation has been investigated mainly in non-human and human primates and dogs, however, there are few data on the presence of negativity/positivity bias in client-cleane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 61 publications
1
37
0
Order By: Relevance
“…Furthermore, studies have reported that people's moral identity is threatened when moral standards conflict with self-interest (Valdesolo and Desteno, 2007;Monin et al, 2009;O'Connor et al, 2020). To reduce cognitive conflict, people often adopt different approaches: when encountering moral standards, people usually avoid MH behaviors; when these behaviors are not avoided, they lower their moral standards to rationalize their hypocritical behavior (López-Pérez and Spiegelman, 2013;Kish-Gephart et al, 2014;Abdai and Miklósi, 2016). For this study, the moral behavior of strangers was undoubtedly the established moral standard.…”
Section: Effects Of the Behavior Of In-group Or Out-group Strangers Omentioning
confidence: 95%
“…Furthermore, studies have reported that people's moral identity is threatened when moral standards conflict with self-interest (Valdesolo and Desteno, 2007;Monin et al, 2009;O'Connor et al, 2020). To reduce cognitive conflict, people often adopt different approaches: when encountering moral standards, people usually avoid MH behaviors; when these behaviors are not avoided, they lower their moral standards to rationalize their hypocritical behavior (López-Pérez and Spiegelman, 2013;Kish-Gephart et al, 2014;Abdai and Miklósi, 2016). For this study, the moral behavior of strangers was undoubtedly the established moral standard.…”
Section: Effects Of the Behavior Of In-group Or Out-group Strangers Omentioning
confidence: 95%
“…This finding is consistent with previous studies that show proselfs tended to be fairer and more generous when their behaviors would be perceived by others ( Van Dijk et al, 2004 ). Proselfs mightuse apparent fairness as a strategy to avoid being perceived as unfair partners by others, since people usually use social evaluation to recognize prosocial and antisocial partners ( Abdai, 2016 ), or to avoid punishment andexclusion in the future ( Henrich et al, 2010 ; Gausel and Leach, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, babies already have a preference for agents who help, rather than hinder others (Hamlin et al, 2007). Such studies are also increasingly done with non-human animals, as reviewed in Abdai and Miklósi (2016). For instance, in a study modeled after Hamlin et al (2007), bonobos unexpectedly showed a preference for hinderers, rather than helpers (Krupenye and Hare, 2018).…”
Section: Prosocial Concernmentioning
confidence: 99%
“…For instance, in a study modeled after Hamlin et al (2007), bonobos unexpectedly showed a preference for hinderers, rather than helpers (Krupenye and Hare, 2018). Abdai and Miklósi (2016) point out that there are still considerable conceptual and procedural issues in animal social evaluation studies, in particular to clearly demonstrate positivity biases. Negativity biases may be taxonomically far more widespread than positivity biases, since the need to avoid harm is universal whereas the need to cooperate is less common.…”
Section: Prosocial Concernmentioning
confidence: 99%
See 1 more Smart Citation